FRI0297 What is the contribution of the antero-posterior radiograph of the lumbar spine to the assessment of radiographic severity and progression using the modified stoke ankylosing spondylitis spine score?. (23rd January 2014) - Maksymowych, W.; Weisman, M.; Lambert, R.; Haroon, N.; Inman, R.; Salonen, D.; Ward, M.; Learch, T.
Abstract : Background: The assessment of radiographic severity and progression in the lumbar spine (LS) of patients with ankylosing spondylitis (AS) is presently assessed only on a lateral radiograph using the modified Stoke Ankylosing Spondylitis Spine Score (mSASSS). This is based on a single report which concluded that the antero-posterior (AP) radiograph contributed additional information relevant to staging and progression in only 12% and 3% of patients, respectively 1 . This observation requires further study because radiographs were read in chronological order and the contribution of the AP to progression was assessed post-hoc by a single reader. Objectives: To determine prospectively to what degree the AP lumbar radiograph influences the assessment of radiographic severity and progression scored by the mSASSS. Methods: Six readers (4 rheumatologists, 2 musculoskeletal radiologists) formed a SPARCC/SPARTAN working group which engaged in the following sequence of steps that preceded a formal scoring exercise: 1. Review of the literature pertaining to radiographic scoring in AS. 2. A pilot exercise in which baseline/2 year radiographs from 25 patients with AS were independently assessed using the mSASSS. 3. Debriefing of discrepant radiographs aimed at adoption of standardized definitions and uniform rules for scoring. 4. Development of a scoring module comprising a reference set of radiographic images clarifying the rules, definitions, and scoring methodology adopted through consensus by the group. A formal scoring exercise was then conducted on 38 patients with AS using the mSASSS in which readers first scored only the lateral radiograph of the LS, then only the AP radiograph, and then both radiographs in combination. Baseline and 2 year radiographs were scored blinded to time point. Scoring of AP radiographs focused on syndesmophytes and ankylosis. Reliability of the mSASSS was assessed by the intraclass correlation method (ICC). Results: Reliability of assessment of radiographic damage was similar on AP radiographs compared to lateral radiographs (Overall ICC for status score for 6 readers =0.91 and 0.87 for lateral and AP radiograph, respectively). Reliability was not further enhanced when both radiographs were assessed simultaneously for either status or change score in the mSASSS. The contribution of the AP radiograph to staging and evaluation of disease progression varied substantially between readers and was most consistent for staging. Conclusions: The contribution of the AP radiograph to the assessment of radiographic severity and progression of disease using the mSASSS affects a higher proportion of patients with AS than documented previously and requires further systematic study. References: Wanders et al. What is the most appropriate radiologic scoring method for ankylosing spondylitis? Arthritis Rheumatism 2004; 50: 2622 Disclosure of Interest: None Declared